Outsiderness and Participation in Liberal and Coordinated Market Economies - Ferragina, Emanuele; Feyertag, Joseph; Seeleib-Kaiser, Martin (PARTECIPAZIONE E CONFLITTO, 2017)
The number of labour market outsiders in Europe has dramatically increased, especially among the youth, potentially influencing social and political participation. Using logistic regressions and comparable survey data – the British Household Panel (BHPS) and the German Socio-Economic Panel (GSOEP) – we connect insights drawn from Varieties of Capitalism and dualization literature with an investigation of individual level outcomes in Britain and Germany. First, we disentangle the impact of skills on outsiderness among the overall population and the youth. Second, we analyse the influence of skills and outsiderness on peo-ple’s social and political participation. We suggest that skills matter in protecting individuals from labour market outsiderness, but they do so in different ways across liberal and coordinated market economies and age groups. While the possession of specific skills reduces the likelihood of being a labour market outsider among young people, it has the opposite effect on political participation. In contrast, education fosters participation but does not reduce the risk of becoming an outsider in the same age cohort. Moreover, although there is no difference between insiders and outsiders when it comes to political par-ticipation, being an outsider may reduce social participation. Finally, young people are more likely to be excluded from social and political participation in Britain than in Germany as a consequence of different welfare and socio-economic systems